WHY DO WE FEEL FEAR? - Makhmudova, Saidaposhakhon (Journal of Contemporary World Studies, 2024)
The article analyzes the main types of fear and how they affect a person. The classification of fears is presented. The types and factors influencing the formation of fears are considered. The results of an experimental study of the influence of anxiety levels on the formation of fears are presented.